New species, Agnoea digitiella sp. nov., of the family Lypusidae (Lepidoptera: Gelechioidea) based on morphology and COI sequences - Kim, Sora; Lee, Seunghwan (Zootaxa, 2020)
In this study, Agnoea digitiella Kim sp. nov. of the little known family Lypusidae are new to science. New taxonomical description and illustrations of its adult and genitalia are provided. Additionally, intra- and inter genetic divergence within the genus, and Neighbor-joining analyses are also supported that A. digitiella sp. nov. is clearly distinguished from congeneric species in the COI gene.